A Prospective, Multicenter, Single-Arm Clinical Trial for Treatment of Complex Diabetic Foot Ulcers with Deep Exposure Using Acellular Dermal Matrix. (September 2019) - Cazzell, Shawn; Moyer, Peter M.; Samsell, Brian; Dorsch, Kimberly; McLean, Julie; Moore, Mark A.
ABSTRACT: OBJECTIVE: This prospective, multicenter study evaluated the efficacy and safety of an acellular dermal matrix allograft, DermACELL (D-ADM; LifeNet Health, Virginia Beach, Virginia), in the treatment of large, complex diabetic foot ulcers (DFUs) that probed to tendon or bone. METHODS: Inclusion criteria were Wagner grade 3 or 4 DFUs between 4 weeks and 1 year in duration. All participants received one application of D-ADM at baseline and could receive one additional application if wound healing arrested. Ulcers were assessed weekly for 16 weeks using a laser measuring device. RESULTS: Sixty-one participants were enrolled, with an average wound area of 29.0 cm 2 ; 59 of these ulcers showed exposed bone. The entire per-protocol population (n = 47) achieved 100% granulation. The mean time to 100% granulation was 4.0 weeks with an average of 1.2 applications of D-ADM. Mean percent wound area reduction was 80.3% at 16 weeks. Those DFUs 15 cm 2 or smaller were substantially more likely to close than DFUs larger than 29 cm 2 ( P = .0008) over a 16-week duration. No complications were associated with the use of the studied matrix. CONCLUSIONS: The D-ADM demonstrated the ability to rapidly reduce the size of large, complex DFUs with exposed bone. Some wounds did not completely heal by 16 weeks; however, the significant reduction in size suggests that these large, complex wounds may heal if given more time.